Conversion Furlow Palatoplasty and the Use of Preoperative Video Nasendoscopy. (May 2022) - Kaye, Alison; Tracy, Meghan; Noel-MacDonnell, Janelle; Dent, Kathryn
Objective: To assess outcomes after conversion Furlow palatoplasty with and without routine preoperative flexible fiberoptic video nasendoscopy (FFVN). Design: Retrospective cohort study. Setting: Tertiary Children's Hospital. Patients: Greater than 3 years of age with cleft palate and velopharyngeal insufficiency (VPI) after straight-line palatoplasty requiring secondary surgery performed with a Furlow palatoplasty. Main Outcome Measures: The number of children with and without routine FFVN prior to conversion Furlow palatoplasty for VPI after initial straight-line palatoplasty. Groups were compared for surgical timing, speech outcomes, and need for additional surgery after conversion Furlow palatoplasty. Results: Fifty-eight patients underwent preoperative FFVN versus 29 without. Mean age at FFVN was 73.8 (SD 34) months. Mean age for secondary palatal surgery by conversion Furlow palatoplasty was 81.5 (SD 34.8) months with FFVN versus 73.4 (SD 34.0) months without FFVN. There was a significant difference ( P < .001) for VPI diagnosis and time to surgery between the groups. Preoperative hypernasality ratings were similar between groups. Postoperatively 65.5% of FFVN and non-FFVN patients corrected to normal resonance. Only 6.9% of all patients rated moderate-severe hypernasality after surgery compared to 42.5% preoperatively. Of total, 5.7% of patients had unchanged hypernasality and only 1 patient rated worse. Seven patients ultimately required additional surgery in attempt to normalize their resonance. Conclusions: Routine preoperative FFVN does not offer any advantage for improved outcomes in children undergoing conversion Furlow palatoplasty after straight-line repair. Routine preoperative FFVN was associated with increased time to surgery after diagnosis of VPI compared to those without FFVN.